Engaging Imam Al-Shatibi's Political Thoughts in Contemporary Contexts - Mohammad Taufiq Rahman; Wan Zailan Kamaruddin Wan Ali (FISIP UIN SGD Bandung, 2021)
This article describes classical Islamic political theory and explores the context of modern politics. The dramatic transformations to the Middle East's political, legal, and economic systems in the 19th and 20th centuries led to systematic secularization, centralization of authority, and westernization. With a literature review, this article raises again the Islamic political teachings initiated by classical fiqh scholars. This study can inspire changes currently resonating with the majority of the middle class, who are dissatisfied with the political power left over from the past. Likewise, this study can provide for those in power amid a wave of democratization in the Islamic world. With this study, Muslims can call back to Shari’a regarding the must, when, how to regulate, and how to resolve the myriad of questions that define how to implement sharia in today's political and economic context.